Comparing targeting strategies for network-based adolescent drinking interventions: A simulation approach. (August 2021) - McMillan, Cassie; Schaefer, David R.
Abstract: Public health researchers and social scientists highlight the promise of network-based strategies to inform and enhance interventions that curb risky adolescent health behaviors. However, we currently lack an understanding of how different variants of network-based interventions shape the distribution of targeted behaviors. The current project considers the effectiveness of five targeting strategies that are designed to have differential impacts on the health of program participants versus non-participants. Using simulations that are empirically-grounded in 28 observed school-based networks from the PROSPER study, we evaluate how these approaches shape long-term alcohol use for intervention participants and non-participants, separately, and consider whether contextual factors moderate their success. Findings suggest that enrolling well-connected adolescents results in the lowest drinking levels for non-participants, while strategies that target groups of friends excel at protecting participants from harmful influences. These trends become increasingly pronounced in contexts characterized by higher levels of peer influence. Highlights: Compare individual and segmentation approaches to network-based interventions. Approaches have different impacts for participant and non-participant alcohol use. Non-participants saw more benefits from individual-based targeting approaches. Tradeoffs emerged for participants and non-participants in segmentation targeting. More positive impacts in contexts defined by higher levels of peer influence.